Prevalence and Correlates of Suicide Ideation and Attempt among Pregnant Women Attending Antenatal Care Services at Public Hospitals in Southern Ethiopia - Belete K (Dove Medical Press, 2021)
Kenean Belete,1 Tilahun Kassew,2 Demeke Demilew,2 Tadele Amare Zeleke2 1Yirgalem Hospital Medical College, Yirgalem, Sidama, Ethiopia; 2Department of Psychiatry, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tilahun KassewDepartment of Psychiatry, College of Medicine and Health Sciences, University of Gondar, P.O.Box: 196, Gondar, EthiopiaTel +251 918410710Email tilahunkassew123@gmail.comBackground: Suicide ideation and attempt are common among pregnant women, risk factors for completed suicide, and associated adverse maternal and fetal outcomes. It is under-recognized and has not been investigated well in low-income countries like Ethiopia. This study aimed to assess the prevalence and factors associated with suicide ideation and attempt among pregnant women attending antenatal care services at public hospitals in southern Ethiopia.Methods: A group of 762 pregnant women who were attending the antenatal service at public hospitals in Hawassa, southern Ethiopia, selected by a systematic random sampling technique, took part in an interview. A Composite International Diagnostic Interview (CIDI) was used to measure suicide ideation and attempt. Chi-square and binary logistic regression analyses were performed to identify the associated factors. An adjusted odds ratio with a 95% confidence interval was used for reporting the result with a p-value< 0.05 statistical significance level.Results: The prevalence of suicide ideation and attempt among pregnant women was 11.8% and 2.7%, respectively. Unplanned pregnancy (AOR=2.01, 95% CI=1.04– 3.88), poor social support (AOR=3.29, 95% CI=1.62– 6.68), common mental disorders (AOR=2.77, 95% CI=1.50– 5.09), and lifetime suicide ideation (AOR=4.63, 95% CI=2.63– 8.16) were factors significantly associated with suicide ideation. Social support was the only correlated factor with suicide attempt among pregnant mothers.Conclusion: The prevalence of suicide ideation and attempt among pregnant women was found to be high. Intervention strategies towards suicidal ideation and attempt should consider improving social support and antenatal related common mental disorders with a primary focus on women with unplanned pregnancy and prior history of suicide ideation.Keywords: antenatal care, pregnant women, suicide, suicide ideation, suicide attempt, Ethiopia